Directory of Accredited Private Home Study Schools Fall 1969. - National Home Study Council, Washington, DC.; National Home Study Council, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
This directory of Accredited Private Home Study Schools, Fall, 1969 lists the 120 schools which have met the following standards set by the National Home Study Council: (1) competent faculty; (2) educationally sound and up-to-date courses; (3) careful screening of students for admission; (4) satisfactory educational services; (5) demonstration of ample student success and satisfaction; (6) reasonable tuition; (7) truthful advertisement of courses; (8) financial ability to provide high quality educational service. The subjects offered are listed alphabetically, followed by the number(s) of schools providing them. (nl)
Availability: Accrediting Commission, National Home Study Council, 1601 Eighteenth Street, N.W., Washington, D.C. 20009.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Standards; Accreditation (Institutions); Correspondence Study; Directories; Proprietary Schools; Units of Study